Effects of Health Education on Hygienic Self-Care Practices among Female Adolescent - Wirata, Resta Betaliani; Ballena, Naressia S (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
Background: As an older child enters the stage of adolescence, several changes happen within the human body, particularly female adolescents. The researcher as a Nurse educator realized the need to include health education on hygienic self-care practices in the subjects to be taught in Junior High School. The study aimed to determine the effect of health education on the hygienic self-care practices among adolescents’ female junior high school in Yogyakarta City, Indonesia. Methods: This study used quantitative design utilized pre-experimental with one group pretest-posttest design. The researcher used health education on the hygienic self-care practices module as the intervention and self-made questionnaire as the instrument. Results: Data shows a mean score on the before health education which is 2.96 had increased after health education to a mean score of 3.68. There is a mean difference of 0.72 and a p-value of 0.000 in between the scores which indicates a significant result. The proposed health education program developed by the researcher needs to be implemented in the participating schools. Conclusion: The role in the collaboration of the school nurses and teachers are needed to the success of a health education program to their students who are in the stage of adolescence.